Fama e infâmia: leituras do romance (ArtCultura, 2011)
A imagem preponderante que se cristalizou de Júlio Ribeiro foi a de autor de um romance considerado obsceno â€” A carne (1888) â€”, elaborada por seus coetâneos e perpetuada na memória histórica. Esse estigma não se restringe ao conteúdo da obra, mas se associa também ao horizonte de leituras (como o escritor foi lido e avaliado) bem como à maneira pela qual sua obra foi transmitida. Nesse sentido, este artigo objetiva enfocar as leituras a respeito do romance A carne como um campo que outorga os significados, sejam da infâmia, sejam da fama, que acompanham o nome do autor. Para tanto, serão examinadas a leitura feita pela crítica literária e a recepção do "grande público", como instâncias contrastantes e concorrentes na configuração da imagem de Júlio Ribeiro..PALAVRAS-CHAVE: Júlio Ribeiro; crítica literária; práticas de leitura.ABSTRACT: The prevalent picture which has been consolidated about Júlio Ribeiro was that of the author of an obscene novel â€” A carne (The fl esh), published in 1888. This opinion was made up by some of his contemporaries and was perpetuated by historical memory. Moreover, it was not limited to the novel's content; on the contrary, it extended itself to the reading horizons, i. e., the ways the author has been read, evaluated and come down to us by tradition. This paper aims to focus on the ways A carne was read and to consider these readings as a sphere which endows the novelist's name with meanings which can be either favoring or infamous. So as to reach our goals, we will analyze how the literary criticism evaluated the mentioned novel, as well as the way the massive audiences read it and understood it. These different points of view will be taken as contestant and contrasting elements in the process of establishing opinions about Júlio Ribeiro..KEYWORDS:Júlio Ribeiro; literary criticism; reading practices.